2016
DOI: 10.1007/s10815-016-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes of singleton siblings: the effects of changing maternal fertility status

Abstract: Declining fertility status, with and without assisted reproductive technology treatment, is associated with increasing risks for adverse outcomes, greatest for women whose fertility status declined the most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Repeated pregnancies themselves may be a contributing factor to the adverse outcomes observed in the commissioned births, although the evidence have been controversial (38,39). One study showed that in a sibling pair, the IVF/ICSI infant born after a previous spontaneous conception was more likely to have low birth weight and preterm birth (40).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated pregnancies themselves may be a contributing factor to the adverse outcomes observed in the commissioned births, although the evidence have been controversial (38,39). One study showed that in a sibling pair, the IVF/ICSI infant born after a previous spontaneous conception was more likely to have low birth weight and preterm birth (40).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of PTB in ART versus SC siblings including two Nordic studies showed an increased risk for PTB in the ART sibling (AOR 1.27, 95% CI 1.08 to 1.49), indicating a risk attributable to the ART treatment per se (Pinborg et al 2013). A sibship study from the USA also showed that subfertile women, with or without ART, were at increased risk for adverse perinatal outcomes when compared with fertile women (Luke et al 2016). Women whose fertility status declined from their first to their second singleton pregnancy had increased risks for adverse outcomes, and the highest risks were observed in those women with the steepest decline in their fertility status (Luke et al 2016).…”
Section: Sibling Studiesmentioning
confidence: 99%
“…A sibship study from the USA also showed that subfertile women, with or without ART, were at increased risk for adverse perinatal outcomes when compared with fertile women (Luke et al 2016). Women whose fertility status declined from their first to their second singleton pregnancy had increased risks for adverse outcomes, and the highest risks were observed in those women with the steepest decline in their fertility status (Luke et al 2016). Thus, subfertility plays a significant role in the adverse outcome in ART although it is not the only contributor.…”
Section: Sibling Studiesmentioning
confidence: 99%
“…This positive trend is due to more appropriate embryo transfer strategies, milder ovarian stimulation, laboratory technological advances, and improved culture media [5]. However, even in singleton pregnancy, after adjustment for maternal confounding factors, the risk of multiple adverse outcomes during the perinatal period, including miscarriage, preterm birth, small for gestational age, low birth weight and gestational hypertension, are higher in IVF-ET pregnancies than in spontaneously conceived pregnancies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%